Knowledge, Attitude, and Practice of Healthcare Providers Toward Novel Coronavirus 19 During the First Months of the Pandemic: A Systematic Review - Gobezie T. Tegegne; Belayneh Kefale; Melaku Tadege Engidaw; Amsalu Degu; Desalegn Tesfa; Amien Ewunetei; Taklo Simeneh Yazie; Mulugeta Molla (Frontiers Media S.A., 2021)
Introduction: Coronavirus disease (COVID-19) is a highly contagious viral infection that has spread to every corner of the world. Lack of knowledge among healthcare providers (HCPs) about diseases such as COVID-19 may delay the diagnosis, disease spread, and produce poor infection control practices. Hence, this systematic review aimed to summarize the knowledge, attitudes, and practices (KAP) of HCPs toward COVID-19 during the first months of the pandemic.Methods: A systematic review was conducted according the PRISMA guidelines, and the protocol was registered on PROSPERO (CRD42020191742). A relevant article search was performed on EMBASE, PubMed, CINAHL, Scopus, and the Google Scholar database. The methodological quality of studies was assessed using the Newcastle-Ottawa Quality Assessment Scale. The median percentage of HCPs with good KAP was computed.Results: Twenty studies involving 12,072 HCPs were included in the review process. Median percentages of 75.8% (IQR: 69.3-87.7%), 74.6% (IQR: 54.4-74.6), and 79.8% (IQR: 67.0-79.8%) of HCPs had good knowledge, and positive attitude and practice, respectively. Although the reported risk factors were inconsistent among studies, age, gender, level of education, experience, infection prevention training, and sources of information were associated with knowledge of HCPs. In addition, being elderly, having a high level of education, absence of chronic illness, and good knowledge and practice were significantly associated with the attitude of HCPs. Further, types of profession, experience, age, level of education, use of personnel protective equipment, and gender were significantly associated with the practice of HCPs.Conclusions: Approximately, three-fourths of HCPs had good knowledge, attitudes, and practices toward COVID-19 during the first months of the pandemic, although the percentage of HCPs was inconsistent in different study settings. In addition, associated factors of KAP were inconsistent among studies; hence, stake holders should target locally identified risk factors to design relevant education packages and infection prevention training to halt the rapid transmission of COVID-19.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020191742, identifier: CRD42020191742.